2019
DOI: 10.51985/jbumdc2019016
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Spondylosis; An Inevitable But Preventable Catastrophe

Abstract: Cervical spondylosis is a chronic degenerative disease which is prevalent in middle and aging population. Its cause is multifactorial attributing to stress, anxiety, trauma, sports, occupational factors or use of handheld devices. It is easily missed and neglected as it has an insidious onset, early subtle features, and resemblance with musculoskeletal problems. It is essential to investigate and intervene because it places a significant impact on health care of individuals and can adversely affect lifestyle b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Fortunately, clinical practice has shown that early abnormal cervical curvature can be corrected through cervical spine posture monitoring and therapeutic intervention, with the process being more effective the earlier it begins [14][15][16] . However, current efforts to address this issue typically rely on either 1) expensive motion capture systems in a laboratory setting or 2) rigid and discrete devices that trigger audio-visual feedback on a smartphone or computer, which may not be practical or convenient for users to monitor and prevent cervical curvature abnormalities [16][17][18][19][20][21][22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, clinical practice has shown that early abnormal cervical curvature can be corrected through cervical spine posture monitoring and therapeutic intervention, with the process being more effective the earlier it begins [14][15][16] . However, current efforts to address this issue typically rely on either 1) expensive motion capture systems in a laboratory setting or 2) rigid and discrete devices that trigger audio-visual feedback on a smartphone or computer, which may not be practical or convenient for users to monitor and prevent cervical curvature abnormalities [16][17][18][19][20][21][22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%